2011
DOI: 10.1074/jbc.m111.243519
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Phospholipid Specificity of Apolipoprotein N-Acyltransferase

Abstract: The enzyme apolipoprotein N-acyltransferase (Lnt) is an integral membrane protein that catalyzes the last step in the posttranslational modification of bacterial lipoproteins. Lnt undergoes covalent modification in the presence of phospholipids resulting in a thioester acyl-enzyme intermediate. It then transfers the acyl chain to the ␣-amino group of the N-terminal diacylglyceryl-modified cysteine of apolipoprotein, leading to the formation of mature triacylated lipoprotein. To gain insight into the catalytic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
68
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(72 citation statements)
references
References 49 publications
4
68
0
Order By: Relevance
“…Similar to previous studies, these data suggested that wildtype Lnt functions in two steps via a ping-pong mechanism ( Fig. 1E) (26). The kinetics of wild-type Lnt reacting with PE in this assay are in line with results reported previously, with a k cat /K m value of 674·M −1 ·s −1 (26).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Similar to previous studies, these data suggested that wildtype Lnt functions in two steps via a ping-pong mechanism ( Fig. 1E) (26). The kinetics of wild-type Lnt reacting with PE in this assay are in line with results reported previously, with a k cat /K m value of 674·M −1 ·s −1 (26).…”
Section: Resultssupporting
confidence: 81%
“…A general two-step ping-pong mechanism for N-acylation by Lnt has been proposed in which a thioester acyl-enzyme intermediate is first formed at the catalytic cysteine through nucleophilic attack on the carbonyl of the sn-1-glycerophospholipid of PE, resulting in S-palmitoylated Lnt. In the second step, the acyl-enzyme intermediate is resolved by nucleophilic attack by the α-amino group of an apolipoprotein, resulting in a mature triacylated lipoprotein (24)(25)(26). Lnt has been shown to exist primarily in the acylated form in vivo, priming it for the more efficient second step of the N-acylation reaction (25).…”
mentioning
confidence: 99%
“…In E. coli, the enzyme functions in a salvage pathway to recycle 2-acyl-GPE formed during the maturation of lipoproteins. Topologically, prolipoproteins are secreted through the inner membrane, and the subsequent processing steps, proteolytic cleavage (18) (Lgt), transfer of the diacylglycerol (19) (Lsp), and N-acylation (20) (Lnt), are located on the outer aspect of the inner membrane. The 2-acyl-GPE cycle is initiated by the transfer of a fatty acid at the 1-position of PE to the amino terminus of the lipoprotein by Lnt (21).…”
mentioning
confidence: 99%
“…Lnt of E. coli has specificity for both the acyl chain length and composition of fatty acids; its preferred substrate is PtdEtn containing a saturated fatty acid (palmitate or C16:0) on sn-1 and an unsaturated fatty acid (oleic acid or C18:1) on sn-2 (3). The sn-1 acyl is transferred to the ␣-amino group of apolipoprotein, but the sn-2 acyl moiety plays an important role (3,4). One possibility is that, because the phospholipid substrate for Lnt changes during the stationary phase, lipoproteins can no longer be N acylated.…”
mentioning
confidence: 99%
“…Signal peptidase II (Lsp) then cleaves the signal peptide, resulting in an apolipoprotein containing a free ␣-amino group. Apolipoprotein N-acyltransferase (Lnt) adds an sn-1-acyl chain derived from phosphatidylethanolamine (PtdEtn) to apolipoprotein, resulting in mature triacylated protein (3,4). The genomes of Firmicutes and Mollicutes do not encode Lnt, and, with only Lgt and Lsp present, one might assume that these bacteria possess only diacylated lipoproteins with unmodified free ␣-amino termini.…”
mentioning
confidence: 99%